Financial management practices of private educational institutions in the National Capital Region - Calderon, Maria Lowella I. (2008)
This study aimed to identify and describe the financial management practices of private educational institutions in NCR. The study utilized the survey research design method. The questionnaire was administered to school finance officers or administrators to gain the desired data, which were analyzed using frequency and percentage distribution and weighted mean to assess the extent of practice of financial management strategies. It was found that there is more convergence in the financial management of private educational institutions. The school finance administrators have established financial management practices including finance policies and similar financial management tools that help them manage their financial resources effectively. The school finance administrators' competencies in relation to finance are crucial in the sustainability and viability of the schools' operations and existence in the years to come.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Computer printout.
Keywords: Education, Secondary -- Philippines -- Manila Metropolitan Area -- Finance; Private schools -- Philippines -- Manila Metropolitan Area -- Finance